Preliminary account on the bryozoans of the Alboran platform (Western Mediterranean), with description of two new species - Ramalho, Laís V.; Rodríguez-Aporta, Raquel; Gofas, Serge (Zootaxa, 2022)
The Alboran platform, located in the Alboran Sea, is an area of high productivity due to the mixture of the Atlantic and Mediterranean waters, which produce an almost permanent upwelling in the region. It has been considered one of the main biodiversity hotspots in the Mediterranean Sea. Previous taxonomic studies on bryozoans carried out around the Alboran platform mentioned a total of 127 species collected at depths between 28 and 480 m. Here we report on four Indemares (Inventario y designación de la Red Natura 2000 en áreas marinas del Estado español) samples collected in 2011 and 2012 at depths between 95 and 120 m from a biogenic gravel bottom (i.e. small rocks and shells). Sixty-eight taxa belonging to 52 genera and 34 families were identified. Two species are proposed as new (Escharella similis n. sp. and Hemicyclopora admirabilis n. sp.), eight taxa were identified only to genus level although two of them (Chorizopora sp., Hippothoa sp.) are likely to be undescribed species, and one taxon only at family level. Among the species identified, 30 are new records for the Alboran platform, 13 are new records for the Alboran Sea, and Microporella funbio is recorded for the first time in the Mediterranean Sea. These results covered only a small part of the material sampled (4 out of 44 samples), which suggests that the number of bryozoan species in the Alboran platform is even higher, and also shows the importance of this area for “bryodiversity”.